Sensor Network Self-Organization Using Random Graphs. (2009) - Brooks Brooks, Richard R. Richard R.
Abstract : Sensor networks are deployed in, and react with, chaotic environments. Self-organizing peer-to-peer networks have admirable survivability characteristics. This chapter discusses random network formalisms for designing, modeling, and analyzing survivable sensor networks. Techniques are given for determining critical values. Applications in system security and surveillance networks are given.